Adsorção de níquel (II) usando leito fixo de carvão ativado em condições subcríticas - Reske, Gabriel Diogo (2020)
In the present work, the use of subcritical conditions in the nickel adsorption process on activated carbon in a fixed bed was investigated in the aqueous medium, with variation of the values for different pressure (from 5 to 25 MPa) and temperature (from 100 to 200 °C) conditions. The evaluation of the effects of these variables on the adsorption operation was carried out through an experimental design for the stoichiometric adsorption capacity. The activated carbon was pre-treated with ultrasound followed by a basic attack with sodium hydroxide and characterized in order to observe changes on the activated carbon before treatment, after treatment, after adsorption and after desorption using X-ray diffraction techniques (XRD), infrared spectroscopy (FTIR) and surface area (BET). The mathematical models in the literature of Thomas, Yoon-Nelson, BDST, Dose-response and Parallel Sigmoidal were analyzed for the description of the rupture curve in the subcritical conditions, the most suitable model for the description of the curves under these conditions was found. Characterization in general showed an increase in the specific area as well as in the surface area due to the pre-treatment on the adsorbent and no significant damage to the structure of the coal throughout the process was observed. An evaluation of the results obtained for the adsorption, in comparison with the process under normal conditions, showed that the performance was greatly increased when used in subcritical conditions, mainly at 25 MPa and 200 °C. The values for the normal condition and the condition of 25 MPa and 200 °C were 1.54 and 6.30 mg g-¹, respectively for the stoichiometric adsorption capacity (Qeq), 5 and 166 min for the rupture time (tr) and 28.31 and 18.71 cm for the mass transfer zone (ZTM). As for the mathematical models, all the proposed models adjusted in general well to the experimental points (R²≥0.957) obtaining the best fit for the Dose-response model (AIC≤-67.28) to describe the curve of rupture in subcritical conditions.